2016
DOI: 10.1080/02640414.2016.1254809
|View full text |Cite
|
Sign up to set email alerts
|

Do cognitive training strategies improve motor and positive psychological skills development in soccer players? Insights from a systematic review

Abstract: Soccer players are required to have well-developed physical, technical and cognitive abilities. The present systematic review, adhering to Preferred Reporting Items for Systematic reviews and Meta-Analysis guidelines, examined the effects of cognitive training strategies on motor and positive psychological skills development in soccer performance and identified the potential moderators of the "cognitive training-soccer performance" relationship. Thirteen databases were systematically searched using keywords re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 50 publications
0
33
1
3
Order By: Relevance
“…In particular, such psychological factors as motivation, psychological skills (PS), and mental toughness (MT) have been considered essential for football performance (Jooste, Steyn & Van Den Berg, 2014). In the current literature, there are many studies concerning the relation of physical factors with football performance, but studies of the influence of psychological factors are somewhat lacking (Slimani, Bragazzi, Tod et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, such psychological factors as motivation, psychological skills (PS), and mental toughness (MT) have been considered essential for football performance (Jooste, Steyn & Van Den Berg, 2014). In the current literature, there are many studies concerning the relation of physical factors with football performance, but studies of the influence of psychological factors are somewhat lacking (Slimani, Bragazzi, Tod et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Soccer is the most common sport in the world and has high mental and physical demands 62 (Slimani et al, 2016;Slimani & Nikolaidis, 2017). It is one of the most complex contact sports 63 whose frequency of practices during the season varies depending on the training phase or 64 competing level (Kirkendall, 2011;Scott & Anderson, 2013).…”
Section: Introduction 61mentioning
confidence: 99%
“…Earlier studies suggested that skilled defenders employed different visual search strategies, regardless of their actual playing position [ 37 39 ]. Also, Slimani et al [ 40 ] concluded that there are differences in practical cognitive/ psychological interventions according to the playing position. Vestberg et al [ 16 ] analyzed the link between EF´s and success in young soccer players.…”
Section: Introductionmentioning
confidence: 99%